Mathematical model of assessment of effect of water supply in engine combustion chamber - A. V. Bizhaev (Сельскохозяйственные машины и технологии)
A water additive in a reciprocating internal combustion engine significantly influences temperature of a working charge in a cylinder that has impact on a toxic substances content in exhaust gases. An analytic technique is necessary for an assessment of water supply effect in the combustion chamber. Due this method, we can receive concrete values of parameters at various power setting, and at changeable ratios of water and fuel. In this regard, a new developed mathematical model makes it possible to find dependences of engine key parameters and to carry out a comparative assessment for systems of water supply in the engine.